2007
DOI: 10.1089/jmf.2006.116
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide Extracted from Rice Bran Fermented withLentinus edodesEnhances Natural Killer Cell Activity and Exhibits Anticancer Effects

Abstract: The objective of this study was to investigate the activation of natural killer (NK) cells and anticancer effects of exo-biopolymer from rice bran cultured with Lentinus edodes [rice bran exo-biopolymer (RBEP)]. Oral administration of RBEP induced the activation of NK cells in a dose-dependent manner. RBEP also prolonged the life spans of mice transplanted with Sarcoma-180 cells and inhibited growing Sarcoma-180 cells in intraperitoneum. Solid tumor growth was also suppressed by oral administration of RBEP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 16 publications
2
44
0
1
Order By: Relevance
“…in previous studies biobran showed immunomodulatory effects on innate (Nk cells, macrophages) as well as on adaptive (T and b lymphocytes) immune system cells [11]. biobran was shown to be a potent enhancer of Nk cell activity [8,9,12], accompanied by increased secretion of TNF-α and iFN-γ. biobran also increased macrophage phagocytosis by induced production of TNF-α, il-6 and nitric oxide [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…in previous studies biobran showed immunomodulatory effects on innate (Nk cells, macrophages) as well as on adaptive (T and b lymphocytes) immune system cells [11]. biobran was shown to be a potent enhancer of Nk cell activity [8,9,12], accompanied by increased secretion of TNF-α and iFN-γ. biobran also increased macrophage phagocytosis by induced production of TNF-α, il-6 and nitric oxide [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran fermented using Saccharomyces cerevisiae has anti-stress and anti-fatigue effects. Furthermore, the polysaccharide extracts of rice bran fermented using Lentinus edodes showed an anti-cancer effect and they prevented defective immune responses; the water extracts of the same fermented rice bran had an anti-photoaging effect [24,25]. Moreover, brown rice fermented using Aspergillus oryzae has a suppressive effect on dextran sulfate sodium-induced ulcerative colitis and it inhibits inflammation-mediated cell infiltration [26,27].…”
Section: Fermentationmentioning
confidence: 99%
“…Other bioactive agents such as garlic extract [128], exo-biopolymer from rice bran [129], and isothiocyanates extract of wasabi [130], as well as flavonoids such as hesperitin, naringenin [131] and chrysin derived from acacia honey [132] have been evaluated for their cytotoxic effect on melanoma cells. A limited number of studies have been effectuated on these compounds with several of them appearing as potential agents against melanoma, but the exact knowledge regarding their active excipient as well as their mechanistic potentials requires extensive in vitro cell culture and in vivo animal model studies to elucidate.…”
Section: Other Multifaceted Food Bioactive Agentsmentioning
confidence: 99%